If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16y + -2 = 19y + 16 Reorder the terms: -2 + 16y = 19y + 16 Reorder the terms: -2 + 16y = 16 + 19y Solving -2 + 16y = 16 + 19y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-19y' to each side of the equation. -2 + 16y + -19y = 16 + 19y + -19y Combine like terms: 16y + -19y = -3y -2 + -3y = 16 + 19y + -19y Combine like terms: 19y + -19y = 0 -2 + -3y = 16 + 0 -2 + -3y = 16 Add '2' to each side of the equation. -2 + 2 + -3y = 16 + 2 Combine like terms: -2 + 2 = 0 0 + -3y = 16 + 2 -3y = 16 + 2 Combine like terms: 16 + 2 = 18 -3y = 18 Divide each side by '-3'. y = -6 Simplifying y = -6
| q^2+11q+18=0 | | 12y+15x=141 | | x^2-6x+9=4x | | 25x-6=45x+2 | | f(x)=2.2(5)x | | T-65=75 | | x=-7+4(1.5) | | 8y-3=10+5 | | -3(5a-4)=132 | | x=-7+4y(1.5) | | 8m-5n=5m+7 | | 6x+20=4x+13 | | log(y)=9t-4 | | 76=x^3+3*x | | 8x+2=7(x-2)+4 | | 15x-12y=141 | | 8+40n-35=-307 | | 4x+72=3x+36 | | 2P=q+5 | | -7+4y-2y+4=0 | | 10=a(43)(3) | | 16+11h=7+9+11h | | -11+13v-19v=3-8v | | -20+7t=-13+7t+2 | | x^2+7x-5= | | 0.5x+x=4.75 | | 5x+118+3x+126= | | 10k-5=-3+10k-2 | | -1/2k=3/4k-3 | | 5.8=-logarithm(Ka) | | -7+6n=7+6n | | -15-9+13p=-13+14p |